Hypersingular integral equations for a thermoelastic problem of multiple planar cracks in an anisotropic medium - Ang, W.T.; Clements, D.L. (Elsevier Ltd., 1999)
The problem of calculating the thermoelastic stress around an arbitrary number of arbitrarily located planar cracks in an infinite anisotropic medium is considered. The cracks open up under the action of suitably prescribed heat flux and traction. With the aid of suitable integral solutions, we reduce the problem to solving a system of Hadamard finite-part (hypersingular) integral equations. The hypersingular integral equations are solved for specific cases of the problem.